MELIHAT FILM “VINA SEBELUM 7 HARI” SEBAGAI GERAKAN ADVOKASI UNTUK KORBAN BULLYING - Dirham Asese (ADISAM PUBLISHER, 2024)
This article discusses advocacy, which is a movement to provide support for marginalized people by highlighting a case of bullying that resulted in death. Vina's case was made into a big screen film and succeeded in attracting a lot of attention from Indonesian citizens. The film